Respuesta :

-(4x - 8y) + 4x + 8y =
-4x + 8y + 4x + 8y =
16y <=== because ur 4x's cancel each other

Answer:

16y

Step-by-step explanation:

[tex]-(4x - 8y) + 4x + 8y[/tex]

Use order of operation to simplify the given expression

Lets start with simplifying the parenthesis

Multiply negative sign inside the parenthesis

[tex]-(4x - 8y) + 4x + 8y[/tex]

[tex]-4x + 8y+ 4x + 8y[/tex]

Now we combine like terms. Combine the terms that has same variables

[tex]-4x + 8y+ 4x + 8y[/tex]

[tex]16y[/tex]